Implementasi Manajemen Strategi dalam Pengembangan Kurikulum Pendidikan Islam: Pengembangan Kurikulum Pendidikan Islam - Fitroh, Miftahul; Wido Supraha; Santi Lisnawati; Nesia Andriana (JPG: Jurnal Pendidikan Guru, 2025)
This research is driven by the quality of education phenomenon, which continues to move and change, and its specifications and qualifications will continue to increase with the times. This study aims to determine the implementation of strategic management in improving the quality of education. This research was conducted at SMA Islam PB Soedirman Bekasi City. The approach taken is qualitative. The method used is the interview, observation, and documentation. The results showed that the strategic management at SMA Islam PB Soedirman Bekasi City had been implemented and was oriented towards improving the quality of education. The conclusions of this research are (1) the strategic management of SMA Islam PB Soedirman Bekasi City begins with formulating a vision and mission that involves internal parties by involving all elements in the school; (2) SMA Islam PB Soedirman Bekasi City has good quality education services, and this is stated in the concept of child-friendly education; (3) SMA Islam PB Soedirman Bekasi City has a good quality educational environment and reflects an Islamic school; (4) SMA Islam PB Soedirman Bekasi City implements the 2013 curriculum by integrating Pendidikan Agama Islam/PAI (Islamic) subjects into each of its subjects; (5) SMA Islam PB Soedirman Bekasi City enroots principles in teachers to become individuals who have the potential to find solutions to every problem. Keywords: Implementation; Strategy management; quality of education